AIR POLLUTION IN PESHAWAR (RATE OF DusTFALL) - Khan, Farid U; Shakita, B; Ghauri, Ejaz G; Ahmad, M (Biological Sciences - PJSIR, 2005)
Rate of dustfall measurements were under taken in urban area of Peshawar at four sites during the period 1993-1998. The average rate of dustfall has increased from 1993 to 1998 and the overall average rate of dustfall was found to be 27.65 tons/km2 month. It was observed that dustfall varied from place to place and from month to month. Meteorological conditions have marked effect on the rate of dustfall pollution. Chemical analysis of the dustfall indicated that it has contribution from particulate emission from automobile exhausts, construction activities, soil and sand particles of the surrounding area.